POSSIBLE PHASE-TRANSFORMATION TOUGHENING OF THERMOSET POLYMERS BY POLY(BUTYLENE TEREPHTHALATE) - KIM, J; ROBERTSON, RE (CHAPMAN HALL LTD, 1992)
Mechanisms were explored by which particles of poly(butylene terephthalate) (PBT) are able to toughen a brittle epoxy. The epoxy studied was an aromatic amine-cured diglycidyl ether of bisphenol-A, which was toughened at about twice the rate with particles of poly(butylene terephthalate) as with particles of nylon 6, poly(vinylidene fluoride), or CTBN rubber. Many of the mechanisms of toughening are visible on the fracture surface of the PBT-epoxy blend, but a mechanism suggested to account for perhaps half of the increased toughness with PBT, phase transformation toughening, is not. The two types of experiment performed to detect phase transformation toughening were: (1) measurements of the rubber cavitation zone in PBT-CTBN rubber-epoxy ternary blends, which would detect an expansion of the PBT particles during fracture if it occurred, and (2) measurements of the fracture energy in PBT-epoxy blends in which the various mechanisms of toughening were selectively suppressed. Both types of experiment indicated the occurrence of phase transformation toughening in these PBT-epoxy blends.
Keywords: ELASTOMER-MODIFIED EPOXIES; CRACK-PROPAGATION; POLY(TETRAMETHYLENE TEREPHTHALATE); MECHANICAL DEFORMATION; FRACTURE-BEHAVIOR; TRANSITION; FAILURE; TOUGHNESS; CERAMICS; RESINS